Prodromal angina and risk of 2-year cardiac mortality in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous intervention. Issue 37 (September 2018) - Ghetti, Gabriele; Bacchi Reggiani, Maria Letizia; Rosetti, Claudia; Battistini, Paola; Lanati, Gianluca; Di Dio, Maria Teresa; Corsini, Anna; Bruno, Matteo; Della Riva, Diego; Bruno, Antonio Giulio; Compagnone, Miriam; Narducci, Riccardo; et al.
Abstract : Abstract: We sought to investigate the prognostic significance of prodromal angina (PA) in unselected patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) and its additive predictive value to the GRACE score. We prospectively enrolled 3015 consecutive STEMI patients undergoing PPCI. Patients were divided in 2 groups according to the presence or absence of PA. Multivariable Cox regression was used to establish the relation to 2-year cardiac mortality of PA. The mean age of the study population was 68 (±14) years; 2178 patients (72%) were male. During follow-up, 395 (13%) patients died with 278 of these (9.2%) suffering from cardiac mortality. Kaplan-Meier estimates showed a survival rate of 95% and 87% for patients with PA and no PA, respectively (log rank test < 0.001). After multivariable analysis, patients with PA had still a lower risk of 2 years' cardiac mortality compared with patients without PA (adjusted hazard ratio = 0.50; 95% confidence interval [CI] 1.06–1.81, P  = .001). Evaluation of net reclassification improvement showed that reclassification improved by 0.16% in case patients, whereas classification worsened in control patients by 1.08% leading to a net reclassification improvement of −0.93% (95% CI: −0.98, −0.88). In patients with STEMI undergoing PPCI the presence of PA is independently associated with a lower risk of 2-year cardiac mortality. However, the incorporation of this variable to the GRACE score slightly worsened the classification of risk. Accordingly, it seems unlikely that the evaluation of PA may be useful in clinical practice.